Ceria–Zirconia Nanoparticles as an Enhanced Multi‐Antioxidant for Sepsis Treatment. (5th July 2017) - Soh, Min; Kang, Dong‐Wan; Jeong, Han‐Gil; Kim, Dokyoon; Kim, Do Yeon; Yang, Wookjin; Song, Changyeong; Baik, Seungmin; Choi, In‐Young; Ki, Seul‐Ki; Kwon, Hyek Jin; Kim, Taeho; et al.
Abstract: The two oxidation states of ceria nanoparticles, Ce 3+ and Ce 4+, play a pivotal role in scavenging reactive oxygen species (ROS). In particular, Ce 3+ is largely responsible for removing O2 − and . OH that are associated with inflammatory response and cell death. The synthesis is reported of 2 nm ceria–zirconia nanoparticles (CZ NPs) that possess a higher Ce 3+ /Ce 4+ ratio and faster conversion from Ce 4+ to Ce 3+ than those exhibited by ceria nanoparticles. The obtained Ce0.7 Zr0.3 O2 (7CZ) NPs greatly improve ROS scavenging performance, thus regulating inflammatory cells in a very low dose. Moreover, 7CZ NPs are demonstrated to be effective in reducing mortality and systemic inflammation in two representative sepsis models. These findings suggest that 7CZ NPs have the potential as a therapeutic nanomedicine for treating ROS‐related inflammatory diseases.